Making rural people’s fate in the hand of urban entities? A question of natural resource governance and rural-urban linkage in Indonesia - Laila Kholid Alfirdaus (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2019)
The idea of rural-urban linkage, which is meant to tackle the issue of urban bias in development, requires trust and equality as fundamental conditions. However, building trust and promoting equality is never easy in rural-urban linkage promotion. Natural resources governance is among the areas which usually show us how difficult it is to promote rural-urban linkage for the hardships in power relations among the actors involved. As having long been noted, the issues of natural resources in Indonesia is contentious; leading to strong debate even conflict. Transparency and accountability often become big questions in natural resources governance, followed with hard deliberation between authorities, companies, and community contrary to the policy. These matters result in further problems of trust, equality, and representation, which further leads to difficulty in rural-urban linkage strengthening. As reflected from mining cases in Central Java and oil palm plantation in Central Kalimantan, we can see clearly how power relations between the pros (usually urban people represented by government apparatus and corporations) and cons (rural people; community) are usually lagging. Policy hardly counts the dissenting voices from the cons. Local authorities decide what is good and not for rural people dealing with natural resources issue. They promote economic development and poverty reduction through natural resources business, which is hardly proven. Natural resources policy is more often made one sided. Sometimes there is repression to suppress against a community that refuses the existence of corporations. This paper discusses challenges to the idea of rural-urban linkages from the experience of natural resources governance in Indonesia. From the cases we studied, we can learn that in order to promote linkage, and, further, equality between rural and urban areas, it is crucial to take into account deliberation, because urban entities are not supposed to make the rural people’s fate, just by exploiting and isolating them from decision making.